Regulation of Estrogen Receptor α Expression in the Hypothalamus by Sex Steroids: Implication in the Regulation of Energy Homeostasis - Xian Liu; Haifei Shi (International Journal of Endocrinology)
Sex differences exist in the complex regulation of energy homeostasis that utilizes central and peripheral systems. It is widely accepted that sex steroids, especially estrogens, are important physiological and pathological components in this sex-specific regulation. Estrogens exert their biological functions via estrogen receptors (ERs). ERα, a classic nuclear receptor, contributes to metabolic regulation and sexual behavior more than other ER subtypes. Physiological and molecular studies have identified multiple ERα-rich nuclei in the hypothalamus of the central nervous system (CNS) as sites of actions that mediate effects of estrogens. Much of our understanding of ERα regulation has been obtained using transgenic models such as ERα global or nuclei-specific knockout mice. A fundamental question concerning how ERα is regulated in wild-type animals, including humans, in response to alterations in steroid hormone levels, due to experimental manipulation (i.e., castration and hormone replacement) or physiological stages (i.e., puberty, pregnancy, and menopause), lacks consistent answers. This review discusses how different sex hormones affect ERα expression in the hypothalamus. This information will contribute to the knowledge of estrogen action in the CNS, further our understanding of discrepancies in correlation of altered sex hormone levels with metabolic disturbances when comparing both sexes, and improve health issues in postmenopausal women.